Glucocorticoids do not cause a clinically relevant elevation in the urine protein-to-creatinine ratio in dogs with inflammatory protein-losing enteropathy - Wood, Cameron J.; Chapman, Peter S.; Horowitz, Cara (Frontiers in Veterinary Science, 2026)
ObjectiveThis study aimed to document changes in the urine protein-to-creatinine ratio (UPC) in dogs with inflammatory protein-losing enteropathy (iPLE) undergoing glucocorticoid therapy and with no overt evidence of concurrent renal disease.MethodsDogs with histologically confirmed iPLE, a serum albumin level of <2.0 g/dL, gastrointestinal signs for ≥2 weeks, and no recent glucocorticoid use were prospectively enrolled at any of the four referral centers between 24 December 2020 and 25 May 2023. Dogs with azotemia, hepatopathy, urinary sediment abnormalities, or confirmed intestinal parasites were excluded. All dogs received prednisone or prednisolone (1 mg/kg BID), clopidogrel, and a new hypoallergenic or low-fat diet. Repeat urinalysis, UPC measurement, urine culture, blood pressure measurement, and serum chemistry analysis were performed after 1–2 weeks (T1) and 2–3 months (T2). Canine chronic enteropathy clinical activity index (CCECAI) scores were assessed at T0 and T1 for correlation with UPC.ResultsTwelve dogs with iPLE were enrolled. Eight dogs were excluded due to comorbidities, loss to follow-up, or euthanasia. The median UPC increased from baseline (0.10) to T1 (0.25) and T2 (0.30). No dog had a UPC of >0.9. Mean CCECAI scores decreased from baseline (8.75) to T1 (3.08). UPC correlated with CCECAI at baseline [ρ (95%CI) 0.71 (0.22–0.91)], but not at follow-up [T1: ρ (95%CI) 0.04 (−0.55–0.60)] or changed from T0 to T1 [ρ (95%CI) 0.15 (−0.67–0.46)].ConclusionGlucocorticoids increase the UPC in dogs with iPLE to the same extent as has previously been shown in healthy dogs.Clinical relevanceClinically significant proteinuria in iPLE dogs treated with glucocorticoids should prompt clinicians to consider alternative etiologies.